MORICA (MORINGA–CARICA) HERBAL TEA: An Innovation in Herbal Tea Based on Carica Fruit and Moringa Leaves for The Health of The Indonesian Archipelago - Nabila Rahma; Akhmad Irfan; Alifah Nur Azizah; Puja Ratna Duhita; Muhammad Fathoni (Center for Intellectual Property and Technology Innovation, Universitas Sains Al-Qur'an, 2025)
Indonesia’s high biodiversity offers significant potential for the development of functional foods based on local resources. One such potential lies in the utilization of carica (Carica pubescens), a distinctive fruit from the Dieng Highlands, whose processing generates substantial peel waste that remains underutilized. At the same time, moringa leaves (Moringa oleifera) are recognized for their high nutritional and bioactive compound content but are limited in consumer acceptance due to their strong grassy flavor. This study aimed to develop an herbal tea bag product combining moringa leaves and carica peel as a sustainable and functional local beverage. An applied research approach was employed through four stages: pre-production, production, analysis, and evaluation. The product was formulated using 2 g of dried moringa leaves and 0.7 g of dried carica peel per tea bag. The results showed that the integration of carica peel improved the sensory characteristics of moringa leaf tea without eliminating its herbal identity, while simultaneously adding value to agro-industrial waste. The production process yielded a practical, consistent, and easily reproducible tea bag product with acceptable sensory quality. This study demonstrates that MORICA Herbal Tea represents a viable model for functional food development that integrates waste utilization, sensory improvement, and sustainability.